Praça Presidente Vargas: luta e resistência na configuração e reconfiguração do espaço público na cidade de Pato Branco - PR - Cardenal, Jozieli Camila (2018)
The present study analyzes moments which took place at the President Vargas Square, located in Pato Branco, Paraná, Brazil, stemmed from the dialogical analysis theory of the speech by Mikhail Bakhtin, with the aim to interpret the public space while utterance built historically. After acknowledging the public space can be conceived while in a relatively stable form, that has a genre, and because of that it cannot be reduced to a finished product, it is made clear that, just as the social dynamics fostered by its actors, the place is in constant transformation. Since it is in continuous movement, it is not finished, resulting in an urban and historical process, of both configuration and reconfiguration, physical and social, which reflects the process of local development.